FILM DOKUMENTER PEMBUATAN SONGKET SILUNGKANG - MERY SILVIA, Dr. Budiwirman, M.Pd, San Ahdi, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Silungkang songket making of documentary aims to introduce to the public, how the creation of songket are still very traditional Silungkang. Workmanship is not an easy thing, So that the people know why the price of songket is expensive, because in its manufacture requires precision and patience. In making this documentary analysis method used is a SWOT analysis as documentary produced will present on all the power (strenght), opportunities (opportunity), and cover all the flaws (weakness) and threats (treatmant) Silungkang songket good that comes from within or from outside to describe a product. Based on the results of the draft design of a media campaign that uses documentary can be a means / media that is able to seize the attention of the public, especially outside of West Sumatra.Keyword: Songket Silungkang, Documentary Film